Navigating through metaproteomics data: A logbook of database searching. Issue 20 (27th April 2015) - Muth, Thilo; Kolmeder, Carolin A.; Salojärvi, Jarkko; Keskitalo, Salla; Varjosalo, Markku; Verdam, Froukje J.; Rensen, Sander S.; Reichl, Udo; de Vos, Willem M.; Rapp, Erdmann; Martens, Lennart; Jagtap, Pratik; et al.
<x xml:space="preserve">Abstract</x> Metaproteomic research involves various computational challenges during the identification of fragmentation spectra acquired from the proteome of a complex microbiome. These issues are manifold and range from the construction of customized sequence databases, the optimal setting of search parameters to limitations in the identification search algorithms themselves. In order to assess the importance of these individual factors, we studied the effect of strategies to combine different search algorithms, explored the influence of chosen database search settings, and investigated the impact of the size of the protein sequence database used for identification. Furthermore, we applied de novo sequencing as a complementary approach to classic database searching. All evaluations were performed on a human intestinal metaproteome dataset. Pyrococcus furiosus proteome data were used to contrast database searching of metaproteomic data to a classic proteomic experiment. Searching against subsets of metaproteome databases and the use of multiple search engines increased the number of identifications. The integration of P. furiosus sequences in a metaproteomic sequence database showcased the limitation of the target‐decoy‐controlled false discovery rate approach in combination with large sequence databases. The selection of varying search engine parameters and the application of de novo sequencing represented useful methods to increase the reliability of the results. Based on our findings, we provide recommendations for the data analysis that help researchers to establish or improve analysis workflows in metaproteomics.